2013
DOI: 10.1177/0268355513517685
|View full text |Cite
|
Sign up to set email alerts
|

Influence of perforating vein surgery in patients with venous ulceration

Abstract: In this series a well-performed SEPS procedure lowers the venous ulcer recurrence rate significantly, indicating the clinical importance of incompetent perforating veins in patients with an active venous ulcer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…A secondary analysis of the Dutch SEPS trial on 94 ulcerated legs was reported with a mean followup of 29 months. 353 Ulcer recurrence was significantly higher in patients who had an incomplete SEPS procedure (P ¼ .007), indicating the clinical significance of incompetent perforating veins in patients with venous ulcers. …”
Section: Guideline 61 Superficial Venous Reflux and Active Venous Lementioning
confidence: 94%
“…A secondary analysis of the Dutch SEPS trial on 94 ulcerated legs was reported with a mean followup of 29 months. 353 Ulcer recurrence was significantly higher in patients who had an incomplete SEPS procedure (P ¼ .007), indicating the clinical significance of incompetent perforating veins in patients with venous ulcers. …”
Section: Guideline 61 Superficial Venous Reflux and Active Venous Lementioning
confidence: 94%
“…After the treatment of PV reflux around the ulcer, the ulcer healed well, and the recurrence rate was low. [2024]…”
Section: Discussionmentioning
confidence: 99%
“…The significance of perforators, their contribution to venous symptoms including ulcer and role of treating them in case of primary varicose veins is disputable. Many studies favour the fact that incompetent perforators contribute to chronic venous disease and need treatment, 5,[14][15][16][17][18] while some disagree. 19,20 The role of incompetent perforators in recurrent or persistent disease and requirement of their treatment are less controversial and there are many supporting studies, some of which have shown incompetent perforators to be the most common cause of recurrence.…”
Section: Discussionmentioning
confidence: 99%